2013
DOI: 10.1063/1.4833569
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of e-beam Al and Hf metal deposition on native oxide InP (100)

Abstract: The interfacial chemistry of thin Al ($3 nm) and Hf ($2 nm) metal films deposited by electron beam (e-beam) evaporation on native oxide InP (100) samples at room temperature and after annealing has been studied by in situ angle resolved X-ray photoelectron spectroscopy and low energy ion scattering spectroscopy. The In-oxides are completely scavenged forming In-In/In-(Al/Hf) bonding after Al and Hf metal deposition. The P-oxide concentration is significantly decreased, and the P-oxide chemical states have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Similar oxidation mechanisms were described in earlier reports for the interaction of different metals with the InP substrate. 31 Narrow scan spectra of the In 3d 5/2 core level of the Ta 1Àx Zr x O/SiO 2 /InP sample are shown in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 99%
“…Similar oxidation mechanisms were described in earlier reports for the interaction of different metals with the InP substrate. 31 Narrow scan spectra of the In 3d 5/2 core level of the Ta 1Àx Zr x O/SiO 2 /InP sample are shown in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 99%
“…The channel material interface with the insulating gate oxide is most crucial in determining the electric performance of metal oxide semiconductor (MOS) based microelectronic devices. The traditional Si/oxide based gate stack is experiencing great challenges when the device downscales to ever-smaller dimensions, evidenced by severely poor reliability and high leakage current. , The III-V/high- k oxide has been regarded as one of the promising candidates in the next generation metal oxide semiconductor field effect transistors (MOSFET) due to its higher carrier mobility and higher breakdown electric field. However, this specific interface structure is suffering from thermal stability, caused mainly by interfacial III-V elemental diffusion, , especially indium (In) diffusion in the postannealing process . The interfacial In diffusion could further cause interfacial gap states and charge traps in oxide, severely undermining device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, extensive studies about In diffusion have been reported. Through low energy ion scattering spectroscopy (LEIS) and angle resolved X-ray photoelectron spectroscopy (ARXPS), Cabrera et al have found that In diffused through HfO 2 after postdeposition annealing (PDA) in HfO 2 /In 0.53 Ga 0.47 As stacks. Dong et al also observed In out-diffusion through high- k dielectric (Al 2 O 3 and HfO 2 ) films grown on InP(100) by atomic layer deposition (ALD) technique.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations